Disruption of the histidine triad nucleotide‐binding hint2 gene in mice affects glycemic control and mitochondrial function123. Issue 5 (22nd April 2013) - Martin, Juliette; Maurhofer, Olivier; Bellance, Nadège; Benard, Giovanni; Graber, Franziska; Hahn, Dagmar; Galinier, Anne; Hora, Caroline; Gupta, Anirudh; Ferrand, Gisèle; Hoppeler, Hans; Rossignol, Rodrigue; et al.
Abstract: The histidine triad nucleotide‐binding (HINT2) protein is a mitochondrial adenosine phosphoramidase expressed in the liver and pancreas. Its physiological function is unknown. To elucidate the role of HINT2 in liver physiology, the mouse Hint2 gene was deleted. Hint2 −/− and Hint2 +/+ mice were generated in a mixed C57Bl6/J × 129Sv background. At 20 weeks, the phenotypic changes in Hint2 −/− relative to Hint2 +/+ mice were an accumulation of hepatic triglycerides, decreased tolerance to glucose, a defective counter‐regulatory response to insulin‐provoked hypoglycemia, and an increase in plasma interprandial insulin but a decrease in glucose‐stimulated insulin secretion and defective thermoregulation upon fasting. Leptin messenger RNA (mRNA) in adipose tissue and plasma leptin were elevated. In mitochondria from Hint2 −/− hepatocytes, state 3 respiration was decreased, a finding confirmed in HepG2 cells where HINT2 mRNA was silenced. The linked complex II‐III electron transfer was decreased in Hint2 −/− mitochondria, which was accompanied by a lower content of coenzyme Q. Hypoxia‐inducible factor‐2α expression and the generation of reactive oxygen species were increased. Electron microscopy of mitochondria in Hint2 −/− mice aged 12 months revealed clustered, fused organelles. The hepatic activities of 3‐hydroxyacyl‐coenzyme A dehydrogenase short chain and glutamate dehydrogenase (GDH) were decreased by 68% and 60%, respectively, without a change in protein expression. GDH activity was similarly decreased in HINT2‐silenced HepG2 cells. When measured in the presence of purified sirtuin 3, latent GDH activity was recovered (126% in Hint2 −/− versus 83% in Hint2 +/+ ). This suggests a greater extent of acetylation in Hint2 −/− than in Hint2 +/+ . Conclusion : Hint2/HINT2 positively regulates mitochondrial lipid metabolism and respiration and glucose homeostasis. The absence of Hint2 provokes mitochondrial deformities and a change in the pattern of acetylation of selected proteins. (HEPATOLOGY 2013)